Guide Conversations Method in Improving Speaking Skills in Kaiwa (Japanese Language Conversation) Learning - Komarudin, Mochamad Arief; Kapoh, Ruty Jacoba; Husain, Sabrina Wardatul Jannah (Jurnal Bahasa Jepang Taiyou, 2023)
This study aims to determine the use of the guide conversation method in improving Japanese speaking skills in kaiwa learning. This study uses the literature study method, which is a research method based on expert opinion about speaking skills in kaiwa learning using the guide conversation method. So it can be concluded that learning Japanese, especially speaking skills, requires various learning strategies. This method offers students a framework and guide to engage in meaningful and productive conversations in Japanese. This journal discusses the main principles and the specific application of the guide conversation method in the context of Japanese language learning, and focuses on improving speaking proficiency, listening comprehension, and cultural understanding of Japanese language students.